2019
DOI: 10.25258/ijddt.v9i3.3
|View full text |Cite
|
Sign up to set email alerts
|

Biological Evaluation of Newly synthesized Spebrutinibm Analogues: Potential Candidates with Enhanced Activity and Reduced Toxicity Profiles.

Abstract: Background: Undoubtedly, cancer is regarded as a major concern for researchers alongside the whole humanity for its high mortality rates. At this moment, there must be some researchers working hard to design, synthesize, and biologically investigate the effects of some potential candidates to fight back cancer. Materials and methods: In previous unpublished work, the authors successfully designed, synthesized, characterized a potential two spebrutinib analogues. Consequently, these analogues were evaluated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…This study found that higher consumption of moderate FODMAP and low FODMAP groups was associated with lower WHR and higher FFM. To explain this association, we have proposed the following hypothesis: a moderate increase in FODMAP consumption was linked to an absolute rise and a relative abundance of microbiota that produce SCFAs [ 41 43 ]. Peroxisome proliferator-activated receptor-γ (PPAR-γ) is a transcription factor whose activity can be modulated by SCFA in this.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that higher consumption of moderate FODMAP and low FODMAP groups was associated with lower WHR and higher FFM. To explain this association, we have proposed the following hypothesis: a moderate increase in FODMAP consumption was linked to an absolute rise and a relative abundance of microbiota that produce SCFAs [ 41 43 ]. Peroxisome proliferator-activated receptor-γ (PPAR-γ) is a transcription factor whose activity can be modulated by SCFA in this.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective cohort study which included 12,245 individuals found that the risk of hypertension was significantly increased in the lowest quartile of vitamin A intake levels [68]. Nitric oxide (NO) is crucial for controlling blood pressure and flow because to its vasodilatory actions [69], NO pathways were shown to be affected by vitamin A, which may contribute to endothelial function [66,70]. Some of the mechanistic pathways involved in the association between DAQS and blood pressure is illustrated in Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…Obeying a restricted protocol that was revealed extensively in previous work, 14 the cell lines were prepared, and the time of the drug candidate application was optimized to be 24 hours. After that, the MTT stock and working solutions were prepared to get homogenized solutions of the cell-medium with 10% MTT to be utilized in the cell-lines.…”
Section: Methodsmentioning
confidence: 99%
“…[11][12][13] In previous work, our team has designed, synthesized, and characterized three potential imatinib derivatives. 14 In this work, the authors aimed to evaluate these derivatives biologically.…”
Section: Research Articlementioning
confidence: 99%